EXPLAINED EXTENSIVE AND INTENSIVE LISTENING - Mirzayeva Gulasal Ergashovna; Bo’ronava MehhamtoshXoliqulovna (Journal of Innovation in Education and Social Research, 2023)
In this article, we will dive deep into the concept of extensive and intensive listening, highlighting their characteristics, purposes, and advantages. We will also provide practical tips for improving your listening skills using both methods, whether for language learning or enhancing your overall communication abilities.